Free radicals after painful stimulation are influenced by antioxidants and analgesics - Rokyta, Richard; Holecek, Václav; Pekárkova, Ivana; Krejcová, Jana; Racek, Jaroslav; Trefil, Ladislav; Yamamotová, Anna (Neuro endocrinology letters, 2003)
OBJECTIVES: To study the balance between the pro-oxidative and antioxidative defence system after repeated painful stimulation in rats and the efficacy of the administration of different antioxidants (vitamins C, E, A, and selenium), analgesics (acetylsalicylic acid, morphine), and their combinations. METHODS: Mechanical clamping of both hind limbs was applied for 10 min for 5 consecutive days in adult male Wistar rats. The tail-flick latency was measured before and after a 5-day nociceptive stimulation with or without the substance application. The reactive oxygen species (ROS) were determined in the sensorimotor cortex. RESULTS: Painful stimulation increased lipoperoxidation which persisted for up to 15 days after it had been discontinued. A simultaneous injection of antioxidants decreased the levels of TBARS, SOD and GSHPx; however, antioxidants applied one week prior to the painful stimulation were ineffective. A simultaneous injection of analgesics reduced stress-induced analgesia caused by the nociceptive stimulation, but did not affect lipoperoxidation. CONCLUSIONS: A combination of antioxidants with analgesics normalized both the oxidative stress and functional (the tail-flick latency) indicators. These results suggest that the administration of antioxidants in pain treatment may be employed to decrease the doses of analgesics and to prevent the negative impact of reactive oxygen species on nociception.
Keywords: Ascorbic Acid; Animals; Antioxidants; Pain Measurement; Morphine; selen; Analgesics, Opioid; Rats, Wistar; Analgesics; Aspirin; Free Radicals; vitamin E; vitamin A; Vitamin A; Vitamin E; Drug Therapy, Combination; měření bolesti; peroxidace lipidů; bolest; opioidní analgetika; Lipid Peroxidation; Male; Selenium; antioxidancia; kyselina askorbová; analgetika; kombinovaná farmakoterapie; krysa rodu Rattus; Pain; morfin; zvířata; mužské pohlaví; Rats; volné radikály; potkani Wistar